The Kinematic Signature of the Warp and Waves in the Milky Way Disk - Sun, Weixiang; Shen, Han; Jiang, Biwei; Liu, Xiaowei (The Astrophysical journal, 2025)
Using over 170,000 red clump (RC) stars selected from LAMOST and APOGEE, we conduct a detailed analysis of the stellar V Z as a function of L Z (or R g ) across different ϕ bins for various disk populations. The V Z of the whole RC sample stars exhibits a wavelike pattern superimposed on an exponentially increasing trend, indicating the contribution from disk warp, disk flare, and disk waves. Our results across various populations suggest that the thin disk is similar to the whole RC sample behavior, while the thick disk displays a wavelike pattern superimposed on a linearly increasing trend, meaning that the features of disk warp and waves are present in both thin and thick disks, and the disk flare feature is only present in the thin disk. These results indicate that the disk warp is potentially driven by secular processes like disk perturbations from intergalactic magnetic fields and a misaligned dark halo. The line-of-node of the disk warp of various populations displays a slight difference, with ϕ 0 = 5 . ° 68 ± 2 . ° 91 for the whole RC sample of stars, ϕ 0 = 5 . ° 78 ± 2 . ° 89 for the thin disk stars, and ϕ 0 = 4 . ° 10 ± 3 . ° 43 for the thick disk stars.